2000
DOI: 10.4269/ajtmh.2000.62.631
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Japanese encephalitis virus from mosquitoes (Diptera: Culicidae) collected in the Western Province of Papua New Guinea, 1997-1998.

Abstract: After Japanese encephalitis (JE) virus emerged in the Torres Strait in Australia in 1995, investigations were initiated into the origin of the incursion. New Guinea was considered the most likely source, given its proximity to islands of the Torres Strait. Almost 400,000 adult mosquitoes were processed for virus isolation from 26 locations in the Western Province of Papua New Guinea (PNG) between February 1996 and February 1998, yielding three isolates of JE virus. Two isolates of Murray Valley encephalitis, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 33 publications
1
109
0
1
Order By: Relevance
“…There has only been one other case of JE identified in humans in PNG, but there is evidence of its presence in mosquito populations. 31,32 The clinical features of acute DF episodes in our cohort were not specific, and we did not observe the typical clinical picture of rash, eye pain, headache, and fever. In our study, dengue was mostly an undifferentiated febrile illness, which is confirmed by the multivariate analysis; it was unable, however, to identify clinical predictors of dengue cases compared with non-dengue/non-malaria cases, except facial flushing and sex (male).…”
Section: Discussionmentioning
confidence: 58%
“…There has only been one other case of JE identified in humans in PNG, but there is evidence of its presence in mosquito populations. 31,32 The clinical features of acute DF episodes in our cohort were not specific, and we did not observe the typical clinical picture of rash, eye pain, headache, and fever. In our study, dengue was mostly an undifferentiated febrile illness, which is confirmed by the multivariate analysis; it was unable, however, to identify clinical predictors of dengue cases compared with non-dengue/non-malaria cases, except facial flushing and sex (male).…”
Section: Discussionmentioning
confidence: 58%
“…Regarding St. Louis encephalitis virus in North America, local persistence in southern regions of the United States rather than annual introduction has become a shared view among some professionals. On the other hand, in northern Australia, a genotyping study provided a supporting evidence of repeated southward invasions of JEV from Papua New Guinea (143).…”
Section: Viral Dispersalmentioning
confidence: 96%
“…Furthermore, a number of the viruses discovered here were found not only in Western Australia but also in regional countries like China and Indonesia, indicating that they infect hosts over a wide geographical area. As the viruses present in these different countries are very similar (95% to ϳ98% nucleotide identities), such limited genetic distance tentatively suggests that these viruses were introduced by windblown mosquitoes (36,37) or by cyclones from neighboring regions (38) or were inadvertently spread by humans, rather than the result of ancient mosquito dispersal. Conversely, based on current data, there appears to be relatively little overlap between the mosquito viromes sampled from Western Australia and those sampled from other parts of Australia (3,10), which may reflect the different mosquito species present in these localities.…”
Section: Figmentioning
confidence: 99%